Sustainable Development Goals Connectivity Dilemma 2019
DOI: 10.1201/9780429290626-15
|View full text |Cite
|
Sign up to set email alerts
|

Urban Analytics Data Infrastructure: Critical SDI for Measuring and Monitoring The National and Local Progress of SDGs

Abstract: This chapter describes an innovative Spatial Data Infrastructure to support urban analytics and urban research capabilities focused on Australian cities, called Urban Analytics Data Infrastructure (UADI). The UADI provides opportunity for multi-disciplinary, and cross-jurisdictional analytics. The chapter highlights the UADI capabilities to be adopted for deriving the SDG indicators as a response to the UN-GGIM strategic framework 2017 -2021 technical requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The 2030 Agenda and the Sustainable Development Goals (SDGs) constitute an existing apparatus for measuring and observing countries based on a specific system that runs into operational problems: current statistical indicators of Sustainable Development (SD) are typically nonspatial and assume a spatial homogeneity related to the scale adopted [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The 2030 Agenda and the Sustainable Development Goals (SDGs) constitute an existing apparatus for measuring and observing countries based on a specific system that runs into operational problems: current statistical indicators of Sustainable Development (SD) are typically nonspatial and assume a spatial homogeneity related to the scale adopted [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…After MDGs, another binding target system was set by the United Nations to fully solve the three dimensions of development, namely social, economic and environmental issues, so as to promote mankind to the path of sustainable development [2]. Subsequently, the global indicator framework formulated by the United Nations Inter-agency Expert Group on SDG Indicators (IAEG-SDGs) provides tools for the world to monitor and evaluate the progress of SDGs [3]. Although the framework is designed for the global country level, international organizations, research institutions, and governments have been actively working to localize the global Indicator Framework so that it can be applied to evaluation at the subnational level.…”
Section: Introductionmentioning
confidence: 99%
“…While this will be explained in the next couple of paragraphs, it is important to mention the role of remote sensing data and analytics in mitigation measures. For instance, this special issue provides an example for exploring the role of urban green spaces and their spatial configuration and extent in mitigating the urban heat island effects [11]. Comparing the land surface temperature and urban green space patterns in Adis Ababa, Ethiopia, Terfa et al (2020) [11] demonstrated the significant role of this methodology to enable urban planners and urban designers to consider the green spaces' spatial configuration to better address the urban heat island effects of urban development.…”
mentioning
confidence: 99%
“…In this special issue, two research studies communicated the role of 3D data and analytics to improve the previous urban analytics. He et al (2021) [12], demonstrated how using 3D urban structure parameters can improve our understanding of seasonal urban land surface temperature. Sanlang et al (2021) [13] introduced an innovative methodology for urban form and functional zoning using light detection and ranging (LiDAR) point clouds and very high-resolution (VHR) images to extract the 3D urban structure parameters and combined them with the spatial patterns of land covers and 2D urban land cover information.…”
mentioning
confidence: 99%